국화 QTL 분석을 이용한 카로티노이드 유전자 기반 화색 판별용 분자표지 개발 - 이예지(Ye-Ji Lee), 원소윤(So Youn Won), 정재아(Jae-A Jung), 김정선(Jung Sun Kim) (Korean journal of breeding, 2025)
Flower color is one of the key trait that determines the marketability of chrysanthemums. However, genetic research on chrysanthemum remains limited because of numerous environmental factors and the complexity of the chrysanthemum genome. To gain a deeper understanding of the genetic mechanisms underlying flower color in chrysanthemum, this study conducted genotyping analysis on 94 F1 progenies derived from a cross between two wild chrysanthemum parents, ‘CWT2’ and ‘CWT8,’ which exhibit distinct flower colors. Genotyping-by-sequencing (GBS) was used for SNP identification, resulting in 79,002 single nucleotide polymorphisms (SNPs). After stringent filtering, 2,548 SNP markers were selected to construct a GBS-SNP linkage map, which was subsequently used to detect quantitative trait loci (QTLs) associated with flower color. Four QTL were identified, encompassing genes involved in carotenoid biosynthesis, carotenoid degradation, and the methylerythritol phosphate pathway. Among the 16 candidate genes analyzed for their potential role in flower color determination, three genes (VDE, CYP707A4, and CYP707A2) were ultimately selected for molecular marker development. The findings of this study provide a valuable foundation for understanding the genetic basis of carotenoid degradation in chrysanthemums. Future in-depth research is expected to facilitate the development of new chrysanthemum varieties for breeding programs through marker-assisted selection in breeding programs. KCI Citation Count: 0